Malingering and functional movement disorder - K. M. Evdokimov; E. Yu. Fedotova; S. N. Illarioshkin (Неврология, нейропсихиатрия, психосоматика)
Functional movement disorders (FMD) are frequently encountered in the clinical practice of neurologists. Recently, the interest of specialists in FMD has increased. Based on neuroimaging, neurophysiological and neuropsychological studies, concepts of the pathophysiology of FMD have been proposed. A difficult issue is differentiation of FMD from factitious disorder and malingering. Diagnostic criteria for FMD, factitious disorder, and malingering are currently proposed, including in ICD-11, but they still contain many controversial provisions, the most important of which are discussed in this article.